New Insights About the Sticking Region in Back Squats: An Analysis of Kinematics, Kinetics, and Myoelectric Activity - Larsen, Stian; Kristiansen, Eirik; van den Tillaar, Roland (Frontiers in Sports and Active Living, 2021)
The aim of this study was to investigate barbell-, joint kinematics, joint kinetics of hip, knee, and ankle in tandem with myoelectric activity around the sticking region in three-repetition maximum (3-RM) back squats among recreationally trained lifters. Unlike previous literature, this study also investigated the event of first peak deacceleration, which was expected to be the event with the lowest force output. Twenty-five recreationally trained lifters (body mass: 70.8±10.5, age: 24.6±3.4, height: 172±8.5) were tested in 3-RM back squats. A repeated one-way analysis of variance showed that ground reaction force output decreased at first peak deacceleration compared to the other events. Moreover, torso forward lean, hip moment arm, and hip contribution to total moment increased, whereas the knee moment arms and moment contribution to total moment decreased in the sticking region. Also, stable moment arms and moment contributions to total moment were observed for the ankle in the sticking region. Furthermore, the knee extensors together with the soleus muscle decreased myoelectric activity in the post-sticking region, while the gluteus maximus and biceps femoris increased myoelectric activity in the post-sticking region. Our findings suggest that the large hip moment arms and hip contributions to total moment together with a lower myoelectric activity for the hip extensors contribute to a poor biomechanical region for force output, and thereby to the sticking region among recreationally trained lifters in 3-RM back squats.